If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (18 + -7n) + 1 = -9 Remove parenthesis around (18 + -7n) 18 + -7n + 1 = -9 Reorder the terms: 18 + 1 + -7n = -9 Combine like terms: 18 + 1 = 19 19 + -7n = -9 Solving 19 + -7n = -9 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-19' to each side of the equation. 19 + -19 + -7n = -9 + -19 Combine like terms: 19 + -19 = 0 0 + -7n = -9 + -19 -7n = -9 + -19 Combine like terms: -9 + -19 = -28 -7n = -28 Divide each side by '-7'. n = 4 Simplifying n = 4
| 3x^2(x^2-7)-x^3(2x)=0 | | -7+4(1+8v)=35 | | -8(9k-7)=17 | | (-3x^3y/9y^2z)^-2 | | 8x+7+4x+43=180 | | 4(2x+6)-3=13x+21-5x | | 30=-5+16+3n | | -4=8-4w | | 5f-9+3=-35 | | 3x^2(x^2-7)=0 | | -81+3x=29-2x | | X=(40-2X) | | -8=3/8n | | -9(1+4d)=19 | | -12x-3y=-12 | | 55=4w-13 | | 3f-11=4 | | -8+9c=19 | | 1/4x=24-1/2x | | 8+9c=19 | | 4/5X1/3= | | -12x-12x^2=0 | | (Z+2)(9x-5)=0 | | 12x+y=-3 | | 2b^2+5b-63=0 | | 261=79-x | | 1/x-1/x+1=1/x(2)+x | | 27-6z=-5(7z-9) | | X*2X=166 | | -16=4y-9 | | 2(8b+2)-1+4g-(2-5g)= | | -x-7=x+1 |